2020
DOI: 10.1016/j.jor.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

InternalBrace has biomechanical properties comparable to suture button but less rigid than screw in ligamentous lisfranc model

Abstract: The aim of this study was to investigate the biomechanical properties of the InternalBrace for lisfranc injuries. Methods: A Sawbone model was developed comparing screw, suture button and InternalBrace. Results: When loaded in axial tension at 0.5 mm/s, the screw was stiffest (2,240 N/mm), while the InternalBrace (200 N/mm) was stiffer than the suture button (133 N/mm). Cyclic loading with 10,000 cycles of 69 N, 138 N, and 207 N showed the InternalBrace maintained stiffness, but fatigued earlier than the sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…7 In a biomechanical model comparing screw, suture button, and Internal-Brace, Hopkins et al demonstrated comparable mechanical properties between the InternalBrace and suture button. 9 These findings and the clinical outcomes reported in the present study demonstrate that the InternalBrace can be a successful flexible fixation option for patients with Lisfranc injuries.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…7 In a biomechanical model comparing screw, suture button, and Internal-Brace, Hopkins et al demonstrated comparable mechanical properties between the InternalBrace and suture button. 9 These findings and the clinical outcomes reported in the present study demonstrate that the InternalBrace can be a successful flexible fixation option for patients with Lisfranc injuries.…”
Section: Discussionsupporting
confidence: 72%
“…7 It offers potential advantages to other ORIF techniques, including avoidance of a second procedure for device removal, collagen ingrowth, reduced iatrogenic cartilage damage, and avoidance of irritation to the tibialis anterior tendon. 7,9 A recent biomechanical study found the InternalBrace to be comparable in stability to transarticular crossed screws. 10 Albeit, since it was approved by the Food and Drug Administration (FDA) in 2019, there are no clinical data reported for patients who underwent ORIF with this device.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,19 In a sawbone model, Hopkins et al demonstrated comparable biomechanical properties of the suture button and InternalBrace. 9 A potential advantage of the InternalBrace is a reduction in iatrogenic damage to the articular surface by using a 1.6-mm K-wire compared with the 2.7- to 3.5-mm drill bit used in the suture button technique. Additional benefits include collagen ingrowth and the avoidance of irritation to the tibialis anterior tendon by using an interference screw that is flush with the cortical surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, during cyclic loading, the InternalBrace has shown suitable anatomical xation properties and provides load-bearing protection [30] . In clinical surgery, for Lisfranc injuries with comminuted fractures of the base of the rst and second metatarsals, both the use of headless compression screws and the suture button technique can only be used as single-plane xation.…”
Section: Discussionmentioning
confidence: 99%